TINDAK PENOLAKAN DALAM FILM TWILIGHT KARYA CATHERINE HARDWICKE (SUATU ANALISIS PRAGMATIK) - TUMALUN, TRILASTY JEYEN ENJEL; JANSEN, FRIEDA TH.; MANUS, JEANE ANGELA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ This research entitled â€œRejection in the film Twilight by Catherine Hardwicke : A Pragmatic Analysisâ€. This research focus on the types and aspects of rejection expressed through the utterances of the characters in the film Twilight. Rejection is a form of communication. It refuses something of the hearer and rejection belongs to perlocutionary act. The research questions should be answer are what are the types of rejection found in this film and how are the aspects of rejection expressed in the film Twilight. The objective of the research are to identify and classify the types of rejection and to analyze and describe the aspects of rejection are expressed in the film. This research used Leech (1983) and Crystal (1978) theory and in collecting data the writer paid attention to the utterances of the characters. The data analyzed descriptively and the result showed that there are some aspects of perlocutionary in terms of direct and indirect rejection, those are to get hearer to think, to get hearer to do, to bring hearer to know, irritate, persuade, frighten, bore, embarrass, and distract attention.Â Â Key Words : Rejection, Film : Twilight,Â  Pragmatics.